The Impact of World Food Price Fluctuation towards Indonesian Macroeconomics - Jami - Ilmia; Regina Niken Wilantari; Agus - Luthfi (Sebelas Maret Business Review, 2017)
Stability of price is a crucial factor for export and import activities, especially food commodities. Indonesia with the characteristics of a small open economy are vulnerable to external price shock as the implication of economic globalization. Understanding the food price shock useful for designing risk mitigation to minimize the effects of shocks to macroeconomic variables. The purpose of this research is to analyze the impact of macroeconomics from Vector Auto-Regression (VAR) methods. The sensitivity of impulse response estimation and variance decomposition which outlines how large and how the effect of the food price shock. Impulse response analysis shows shocks on global food price got the response by fastest and the most powerful by inflation. While the description of variance decomposition, variation described by economic growth. The results show that the global food price affects economic growth that is transmitted through inflation.